2006
DOI: 10.1111/j.1461-0248.2006.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed evolution after crop gene introgression: greater survival and fecundity of hybrids in a new environment

Abstract: Crop-wild hybridization may produce offspring with lower fitness than their wild parents due to deleterious crop traits and outbreeding depression. Over time, however, selection for improved fitness could lead to greater invasiveness of hybrid taxa. To examine evolutionary change in crop-wild hybrids, we established four wild (Raphanus raphanistrum) and four hybrid radish populations (R. raphanistrum x Raphanus sativus) in Michigan (MI), USA. Hybrid and wild populations had similar growth rates over four gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
230
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(248 citation statements)
references
References 56 publications
14
230
2
1
Order By: Relevance
“…Typically F 1 hybrids produce approximately 50 -60% aborted pollen grains (Snow et al ., 2001). We found that F 1 hybrids can produce as many seeds as their wild relative (but see Snow et al ., 2001), and in some environments the fitness of advanced-generation hybrids may greatly exceed that of their weedy progenitor (Campbell et al ., 2006). Cultivated and wild radish species were introduced into California by the nineteenth century, and Panetsos & Baker (1967) suggested that 'introgression of raphanistrum characters appears to have been a major factor in converting the erstwhile crop plant, R. sativus , into a highly successful weed.'…”
Section: Study Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically F 1 hybrids produce approximately 50 -60% aborted pollen grains (Snow et al ., 2001). We found that F 1 hybrids can produce as many seeds as their wild relative (but see Snow et al ., 2001), and in some environments the fitness of advanced-generation hybrids may greatly exceed that of their weedy progenitor (Campbell et al ., 2006). Cultivated and wild radish species were introduced into California by the nineteenth century, and Panetsos & Baker (1967) suggested that 'introgression of raphanistrum characters appears to have been a major factor in converting the erstwhile crop plant, R. sativus , into a highly successful weed.'…”
Section: Study Systemmentioning
confidence: 99%
“…1; part of a larger study described in Campbell et al ., 2006). The six populations were separated from each other and from local wild radish populations by at least 1 km, which is far enough to avoid unintended gene flow via pollinators (Ellstrand & Marshall, 1985 (Campbell et al ., 2006). Each spring through 2004, the plots were tilled, fertilized and handweeded for 2 wk to simulate agricultural management and to promote population persistence.…”
Section: Seed Sources For Experimental Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of hybridization between polyploid cultivars and diploid relatives, chromosomal imbalances may add to a low fitness of hybrids (Hauser et al, 1998a). However, hybrids between cultivated and wild plants may sometimes exhibit improved fitness relative to their parents (Ellstrand, 2003), due to inheritance of beneficial crop alleles (Campbell et al, 2006), heterosis (Hauser et al, 1998b), and novel combinations of genes and traits of the parents (Hauser et al, 1998a;Hooftman et al, 2005). Transgression of traits from the two parents is thought to be a major mechanism for creating evolutionary novelties in hybrids (Lexer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%